ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEMISKINAN DI KABUPATEN/KOTA PROVINSI BALI - Darma Yanti, Ni Putu Nonik Sri; Ayuningsasi, Anak Agung Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.04.TAHUN.2024, 2024)
Poverty is a condition of life that is completely lacking experienced by a person or household so that he is unable to meet the needs that are proper for his life. Poverty has become a complex and chronic problem at the national and regional levels so overcoming it requires appropriate and sustainable strategies. The purpose of this study was to analyze the effect of PAD, PDRB, unemployment, HDI, and population simultaneously and partially on poverty in districts/cities of Bali Province. The data used is secondary data in the districts/cities of Bali Province from 2015-2020 sourced from the BPS Provinsi Bali (Central Statistics Agency for the Province of Bali), with a total of 54 observations. The analysis technique used is panel data regression analysis which is then followed by multiple linear regression analysis. Based on the results of data analysis, it is known that PAD, PDRB, unemployment, HDI, and total population simultaneously have a significant effect on poverty in districts/cities of Bali Province. PAD and HDI have no significant effect on poverty, population and unemployment have a positive and significant effect on poverty, and PDRB has a negative and significant effect on poverty in districts/cities of Bali Province.